Filamentation due to the Weibel Instability in two counterstreaming laser ablated plasmas. (May 2016) - Dong, Quan-Li; Yuan, Dawei; Gao, Lan; Liu, Xun; Chen, Yangao; Jia, Qing; Hua, Neng; Qiao, Zhanfeng; Chen, Ming; Zhu, Baoqiang; Zhu, Jianqiang; Zhao, Gang; et al.
Abstract: Weibel-type filamentation instability was observed in the interaction of two counter streaming laser ablated plasma flows, which were supersonic, collisionless, and closely relevant to astrophysical conditions. The plasma flows were created by irradiating a pair of oppositely standing plastic (CH) foils with 1ns-pulsed laser beams of total energy of 1.7 kJ in two laser spots. With characteristics diagnosed in experiments, the calculated features of Weibel-type filaments are in good agreement with measurements.